PENURUNAN KOLESTEROL PADA SUSU SINGKONG TERMODIFIKASI DENGAN PENAMBAHAN BIJI PEPAYA YANG DIAPLIKASIKAN PADA TIKUS DISLIPIDEMIA - Sazila K. Rahman; Muhammad Hasan Albana; Rian Nugraha Putra; Muthia Elma (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2017)
Abstract. Cassava has a low selling value because it contains cyanide acid (HCN) which is deadly, while papaya seeds contain flavonoids, tannins and saponins are beneficial to health. How to increase the selling value of cassava and papaya seeds by processing modified cassava milk with the initial method, ie cleaned cassava, soaked 72 hours with 4% w / v NaHCO3, soaked 1 hour with 15% w / v salt, soaked 24 hours with 0,1% w / w starter Bimo-Cf, then stirred at 75-80 oC and fermented for 3 days using Fermipan (Saccharomyces cerevisiae) and Raprima (Rhizopus oryzae). The fermentation results were added aquadest and papaya seeds (20 and 40% w / w) stirred at 70-75 oC. Then dried to produce modified cassava milk. Modified cassava milk was intervened in mice for 28 days with dysplinemic treatment. The results showed the greatest decrease in HCN content in modified cassava milk with addition of 40% w / w of papaya seeds at Saccharomyces cerevisiae (2.052 ppm) and Rhizopus oryzae (2,160 ppm). The best increase in protein content was obtained by addition of 40% w / w of papaya seeds in Rhizopus oryzae (4.06%) and Saccharomyces cerevisiae (3.30%). The decrease of total cholesterol total of the best dysplinemic rats was obtained from modified cassava milk of R. Oryzaae variation with the addition of 20% papaya seeds by 60.45% and 40% papaya seeds by 40.63%..Keywords: papaya seed, cholesterol, Rhizopus oryzae, Saccharomyces cerevisiae, cassava.